Characterization of a gene cluster for exopolysaccharide biosynthesis and virulence in Erwinia stewartii. - Dolph, P J (1988)
We have previously cloned the genes for synthesis of capsular polysaccharide (cps) and slime from Erwinia stewartii in cosmid pES2144. In this study, pES2144 was shown to complement 14 spontaneous cps mutants. These mutants were characterized by probing Southern blots of mutant genomic DNA with pES2144; insertions were detected in four mutants and deletions in six mutants. Genetic and physical maps of the pES2144 cps region were constructed by subcloning, restriction analysis, and transposon mutagenesis with Tn5, Tn5lac, and Tn3HoHo1. Mutations affecting the ability of pES2144 to restore mucoidy to cps deletion mutants were located in five regions, designated cpsA to cpsE. None of the cps mutants were able to cause systemic wilting of corn plants, and mutations in cps regions B to E further abolished the ability of the bacterium to cause watersoaked lesions on seedlings. The gene for uridine-5'-diphosphogalactose 4-epimerase (galE) was linked to the cps genes on pES2144. In E. stewartii, galE was constitutively expressed, whereas the genes for galactokinase (galK) and galactose-1-phosphate uridyltransferase (galT) were inducible and not linked to galE. Thus, galE does not appear to be part of the gal operon in this species.